2015
DOI: 10.1186/s12944-015-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of apolipoprotein E (ApoE) polymorphisms with risk of primary hyperuricemia in Uygur men, Xinjiang, China

Abstract: BackgroundApolipoprotein E (ApoE) participates in lipoprotein metabolism and immune regulation. This study assessed association between ApoE polymorphisms with hyperuricemia and uric acid metabolism in Uygur men, Xinjiang, China.MethodsA total of 474 hyperuricemia patients and 518 healthy male controls were recruited from the Health Screening Center, Uygur region of Xinjiang, China and subjected to ApoE genotyping using a multiplex amplification refractory mutation system PCR.ResultsApolipoprotein E3/3 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
10
1
1
Order By: Relevance
“…Our co-expression analysis also indicates that HNF4A , is co-expressed with LINC01229 but not MAFTRR , consistent with the SUA2 LINC01229 eQTL and the coincidental expression of the SUA2 enhancer and hnf4a . LINC01229 and HNF4A also share enriched GO terms in lipid relevant pathways that involve genes with (albeit unreplicated) reports of association with urate (e.g., ApoE ) (Sun et al, 2015) and gout (e.g., ABCG1 and ABCA1 ) (Lai et al, 2012) (Supplementary Figure S14).…”
Section: Discussionmentioning
confidence: 72%
“…Our co-expression analysis also indicates that HNF4A , is co-expressed with LINC01229 but not MAFTRR , consistent with the SUA2 LINC01229 eQTL and the coincidental expression of the SUA2 enhancer and hnf4a . LINC01229 and HNF4A also share enriched GO terms in lipid relevant pathways that involve genes with (albeit unreplicated) reports of association with urate (e.g., ApoE ) (Sun et al, 2015) and gout (e.g., ABCG1 and ABCA1 ) (Lai et al, 2012) (Supplementary Figure S14).…”
Section: Discussionmentioning
confidence: 72%
“…There is a greater risk for CMB in male APOE4 carriers than in female APOE4 carriers . Moreover, APOE4 is associated with an increased risk for hyperuricemia in Chinese men . This suggests that different manifestations of CMB according to APOE4 carrier status may contribute to the observed sex differences.…”
Section: Discussionmentioning
confidence: 96%
“…The genetical background may have a potential influence in the prevalence of hyperuricemia among these different ethnic groups except lifestyle, a major factor. For example, previous studies reported that gene polymorphism in Uygur Chinese may be correlated with hyperuricemia such as ApoE E4, IL-8, IL-1RL1, IL-18 and SLC17A1 genes [48][49][50]. Hyperuricemia is a complicated metabolic disease with many risk factors.…”
Section: Discussionmentioning
confidence: 99%